HOW GENDER IS NAMED IN UNISEX PERFUMES: A SOCIO-ONOMASTIC APPROACH - Kurniawati, Sonia; Handayani, Wiwik Retno (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
Perfume has long been used as a body fragrance, but in today’s world, its role extends far beyond mere scent enhancement. It has evolved into a significant aspect of personal identity, self-expression, and lifestyle. In fact, perfume is often perceived as a symbolic presentation of one’s character, emotions, social status and even cultural identity. This article explored gender representation in unisex perfume names using a socio-onomastics approach. This study analyzed a dataset of 3,390 unisex perfume names from 2017-2024 sourced from Fragrantica. Sketch Engine toolkit was used to measure word frequency and concordance. Finally, the findings revealed five primary naming references: specific natural elements, inventors or manufacturers, places of origin, materials and identity-related and gender-stereotyped. Among the identified, material-based naming was the most dominant particularly through references to floral, fruity, and woody elements. Although no specific words explicitly indicated a unisex representation or any association, some findings disclosed that terms traditionally linked to either masculinity or femininity were not always intended exclusively for that particular gender. In short, this showed the effort to break traditional gender boundaries. Nonetheless, it was found that names referring to males had a higher frequency compared to names referring to females, meaning that gendered elements in naming unisex perfume names remain exist.